Learning distractions: a study in UiTM Kedah / Azfahanee Zakaria, Sarah Sabir Ahmad and Syed Mohammed Alhady Syed Ahmad Alhady - Zakaria, Azfahanee; Sabir Ahmad, Sarah; Syed Ahmad Alhady, Syed Mohammed Alhady (Universiti Teknologi MARA Cawangan Kedah, 2022)
Concentration has been one of the most crucial indicators of a student’s learning quality. As the level of education rises, the attention towards the online learning is seen lowers. Therefore, in order to remain focus and able to concentrate on what is being taught, students need to ensure that they are not easily distracted. Distractions may arise from both internal or external sources. This research looks into how technology, the classroom environment, and emotion which may distract students in learning and focusing on their academics. One hundred student from the Faculty of Business Administration of UITM Kedah, have responded to the study. The findings indicated that students are distracted most due to emotions and class environment. However, technology allows the students to venture positively towards online learning.